2016
DOI: 10.1021/acsbiomaterials.6b00502
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Poly(amine-co-ester-co-orthoester) for Efficient and Safe Gene Delivery

Abstract: Cationic polymers are used for non-viral gene delivery, but current materials lack the functionality to address the multiple barriers involved in gene delivery. Here we describe the rational design and synthesis of a new family of quaterpolymers with unprecedented multifunctionality: acid sensitivity, low cationic charge, high hydrophobicity, and biodegradability, all of which are essential for efficient and safe gene delivery. The polymers were synthesized via lipase-catalyzed polymerization of ortho ester di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…There is also precedent for polyplexes lyophilized with excipients having improved activity over the freshly prepared parent formulation. For example, Zhang et al demonstrated a trehalose dose-dependent increase in transfection efficiency for lyophilized poly(amine-co-ester-co-orthoester) (oPACE) polyplexes for gene delivery, with polyplexes lyophilized in 158 mM trehalose nearly doubling the transfection efficiency relative to fresh oPACE-pDNA polyplexes [37]. Thus, our results suggest that results from polyplexes used for gene delivery are relevant and can be extrapolated to the PPAA-based polyplexes designed for delivery of cationic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…There is also precedent for polyplexes lyophilized with excipients having improved activity over the freshly prepared parent formulation. For example, Zhang et al demonstrated a trehalose dose-dependent increase in transfection efficiency for lyophilized poly(amine-co-ester-co-orthoester) (oPACE) polyplexes for gene delivery, with polyplexes lyophilized in 158 mM trehalose nearly doubling the transfection efficiency relative to fresh oPACE-pDNA polyplexes [37]. Thus, our results suggest that results from polyplexes used for gene delivery are relevant and can be extrapolated to the PPAA-based polyplexes designed for delivery of cationic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The same group synthesized a series of poly(amine-co-ester-co-orthoester) with acid sensitivity and redox-responsive, these polyesters have been proved to be gene delivery and nanocarriers for doxorubicin delivery. 93,98,101 Similarly, Liu et al developed the terpolymerization cationic poly(amine-co-ester) for DNA condensation with PEG shell for nanoparticle stabilization and poly(glutamic acid) and mTAT (a cell-penetrating peptide) for accelerating cellular uptake, and a nuclear localization signal peptide for enhanced intracellular transport of DNA to the nucleus. 102 Such an approach presents a more sustainable and environmentally friendly synthesis and could also be used for controlled drug release and gene delivery.…”
Section: Combination Of Ring-opening Polymerization and Polycondensationmentioning
confidence: 99%
“…New lipids and polymers have been developed with the goal of improving nucleic acid delivery in vitro and in vivo , and these could prove useful for delivering editing agents. For example, poly(amine-co-ester) terpolymers have been used to successfully deliver pDNA in vivo [47, 48], and have recently been shown to effectively deliver TFO PNAs ex vivo (A.S. Piotrowski-Daspit et al, abstract 614, 21 st Annual Meeting of American Society of Gene & Cell Therapy, Chicago IL, May 2018). Additionally, the incorporation of targeting moieties such as antibodies for specific cell types could be useful particularly for local delivery.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%